Sejarah dan perkembangna ejaan bahasa indonesia - Ruhii, Siti Rohimin (Maliki Interdisciplinary Journal, 2026)
This article examines the historical development of Indonesian spelling from the colonial era to the modern period and its relevance to contemporary communication. Using a literature review approach, the study analyzes various historical sources and official language regulations. The findings reveal that spelling reforms evolved alongside sociopolitical dynamics and the need for standardized national language usage. Indonesian spelling has undergone several transformations. Each reform seeks to enhance clarity, efficiency, and consistency in written communication. This article also discusses modern challenges in the application of standard spelling, such as digital language trends, slang usage, and foreign word adoption. The study highlights the importance of accurate spelling as a foundation to literacy and the preservation of national linguistic identity.